Specific features of speech development in mentally retarded children (Eurasian Journal of Humanities and Social Sciences, 2025)
The article discusses the specific features of speech development in mentally retarded children, the characteristics of the mental development of a mentally retarded child, motor disorders, their impact on the voluntary pronunciation of sounds in speech, as well as on the pronunciation of words, and the importance of speech development in orientation to social and everyday life.